2017
DOI: 10.18488/journal.1007/2017.7.4/1007.4.75-83
|View full text |Cite
|
Sign up to set email alerts
|

Export market diversification and export performance of Sri Lanka: a cointegration analysis

Abstract: This paper aims to investigate the existence of geographical export market diversification and its relations with export performance of Sri Lanka. The paper identifies the existence of geographical export market diversification by using Herfindahl Index, and empirically investigates the long run and the short run relationship between market diversification and export performance. The time series data extracted from the World Bank database are used to construct Index and appropriate variables. Johansen's cointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Meanwhile, research conducted by Mwakanemela (2014); Nguyen (2014); Majeed and Eatzaz (2006); etc. Bhavan (2016) suggests that rising Foreign Direct Investment (FDI) may increase export growth. This reinforces the opinion that rising FDI could provide a meaningful increase for Indonesia's export growth.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, research conducted by Mwakanemela (2014); Nguyen (2014); Majeed and Eatzaz (2006); etc. Bhavan (2016) suggests that rising Foreign Direct Investment (FDI) may increase export growth. This reinforces the opinion that rising FDI could provide a meaningful increase for Indonesia's export growth.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated export diversification has a significant and positive impact on economic growth. Thangamani (2017) also conducted a study that concluded export diversification can promote export performance in Sri Lanka. Furthermore, increasing the product diversifies of export also can help to stabilize the export revenues and to encourage earning from export.…”
Section: Introductionmentioning
confidence: 99%